Sex‐Related Differences in Rat Choroid Plexus and Cerebrospinal Fluid: A cDNA Microarray and Proteomic Analysis. (20th January 2016) - Quintela, T.; Marcelino, H.; Deery, M. J.; Feret, R.; Howard, J.; Lilley, K. S.; Albuquerque, T.; Gonçalves, I.; Duarte, A. C.; Santos, C. R. A.
Abstract : The choroid plexus (CP) epithelium is a unique structure in the brain that forms an interface between the peripheral blood and the cerebrospinal fluid (CSF), which is mostly produced by the CP itself. Because the CP transcriptome is regulated by the sex hormone background, the present study compared gene/protein expression profiles in the CP and CSF from male and female rats aiming to better understand sex‐related differences in CP functions and brain physiology. We used data previously obtained by cDNA microarrays to compare the CP transcriptome between male and female rats, and complemented these data with the proteomic analysis of the CSF of castrated and sham‐operated males and females. Microarray analysis showed that 17 128 and 17 002 genes are expressed in the male and female CP, which allowed the functional annotation of 141 and 134 pathways, respectively. Among the most expressed genes, canonical pathways associated with mitochondrial dysfunctions and oxidative phosphorylation were the most prominent, whereas the most relevant molecular and cellular functions annotated were protein synthesis, cellular growth and proliferation, cell death and survival, molecular transport, and protein trafficking. No significant differences were found between males and females regarding these pathways. Seminal functions of the CP differentially regulated between sexes were circadian rhythm signalling, as well as several canonical pathways related to stem cell differentiation, metabolism and the barrier function of the CP. The proteomic analysis identified five down‐regulated proteins in the CSF samples from male rats compared to females and seven proteins exhibiting marked variation in the CSF of gonadectomised males compared to sham animals, whereas no differences were found between sham and ovariectomised females. These data clearly show sex‐related differences in CP gene expression and CSF protein composition that may impact upon neurological diseases.